Synthesis, Characterization And Antitumor Activity Of Copper(II) Complexes, [CuL2] [HL1-3=N,N-Diethyl-N'-(R-Benzoyl)Thiourea (R=H, o-Cl and p-NO2)] - Wilfredo Hernández; Evgenia Spodine; Lothar Beyer; Uwe Schröder; Rainer Richter; Jorge Ferreira; Mario Pavani (Bioinorganic Chemistry and Applications)
The copper (II) complexes (CuL2) were prepared by reaction of Cu(CH3COO)2 with the corresponding derivatives of acylthioureas in a Cu:HL molar ratio of 1:2. Acylthiourea ligands, N,N-diethyl-N'-(R-benzoyl) thiourea (HL1-3) [R=H, o-Cl and p-NO2] were synthesized in high yield (78-83%) and characterized by elemental analysis, infrared spectroscopy, 1H and 13C NMR spectroscopy. The complexes CuL2 were characterized by elemental analysis, IR, FAB(+)-MS, magnetic susceptibility measurements, EPR and cyclic voltammetry. The crystal structure of the complex Cu(L2)2 shows a nearly square-planar geometry with two deprotonated ligands (L) coordinated to CuII through the oxygen and sulfur atoms in a cis arrangement. The antitumor activity of the copper(II) complexes with acylthiourea ligands was evaluated in vitro against the mouse mammary adenocarcinoma TA3 cell line. These complexes exhibited much higher cytotoxic activity (IC50 values in the range of 3.9-6.9 μM) than their corresponding ligands (40-240 μM), which indicates that the coordination of the chelate ligands around the CuII enhances the antitumor activity and, furthermore, this result confirmed that the participation of the nitro and chloro substituent groups in the complex activities is slightly relevant. The high accumulation of the complexes Cu(L2)2 and Cu(L3)2 in TA3 tumor cells and the much faster binding to cellular DNA than Cu(L1)2 are consistent with the in vitro cytotoxic activities found for these copper complexes.